Assessing the volcanic hazard for Rome: 40Ar/39Ar and In‐SAR constraints on the most recent eruptive activity and present‐day uplift at Colli Albani Volcanic District. Issue 13 (12th July 2016) - Marra, F.; Gaeta, M.; Giaccio, B.; Jicha, B. R.; Palladino, D. M.; Polcari, M.; Sottili, G.; Taddeucci, J.; Florindo, F.; Stramondo, S.
Abstract: We present new 40 Ar/ 39 Ar data which allow us to refine the recurrence time for the most recent eruptive activity occurred at Colli Albani Volcanic District (CAVD) and constrain its geographic area. Time elapsed since the last eruption (36 kyr) overruns the recurrence time (31 kyr) in the last 100 kyr. New interferometric synthetic aperture radar data, covering the years 1993–2010, reveal ongoing inflation with maximum uplift rates (>2 mm/yr) in the area hosting the most recent (<200 ka) vents, suggesting that the observed uplift might be caused by magma injection within the youngest plumbing system. Finally, we frame the present deformation within the structural pattern of the area of Rome, characterized by 50 m of regional uplift since 200 ka and by geologic evidence for a recent (<2000 years) switch of the local stress‐field, highlighting that the precursors of a new phase of volcanic activity are likely occurring at the CAVD. Key Points: The time elapsed since the last eruption overruns the recurrence time in the last 100 kyr Maximum uplift rates (>2 mm/yr) are concetrated in the area hosting the most recent (<200 ka) vents We suggest that the observed uplift might be the result of magma injection within the youngest plumbing system of the volcano